The Impact of Emotion on Musical Long-Term Memory - Nineuil, Clémence; Dellacherie, Delphine; Samson, Séverine (Frontiers in Psychology, 2020)
The influence of emotional dimensions such as arousal and valence on memory has been a topic of particularly intense inquiry. As stimuli go, music is capable of provoking strong emotional responses from listeners, which can in turn influence memory. However, few studies have examined the effect of musical emotions on memory, and even fewer the effect of valence and arousal. In order to shed light on the ways in which emotional dimensions affect musical memory as study-test delay intervals increase, we tested recognition after a short delay and after a long delay. In line with the literature, we hypothesized an emotional enhancement of music memory induced by post-encoding processes leading to better recognition of musical excerpts in delayed condition, as compared to the immediate condition. The effects of arousal and valence were expected to become exaggerated after a long delay. We also predicted that the two emotional dimensions would be differently affected by the study-test intervals. Our results showed that the emotional enhancement of memory depends upon the valence, with remembering of positive and negative stimuli being differently affected by the duration of the study-test delay interval. Furthermore, our data demonstrated that musical excerpts were better recognized after a long than after a short delay, illustrating that memory consolidation for musical information is taking place during the long study-test interval. Moreover, musical memory consolidation is strongly related to the characteristics of the positive valence, which have been discussed in relation to its pleasantness. This original finding provides new insights into the modulatory effects of emotional valence on memory consolidation and could offer promising therapeutic possibilities for the rehabilitation of memory disorders.